Seed rain generated by bats under Cerrado’s pasture remnant trees in a Neotropical savanna - Ragusa-Netto,J. (2015)
Abstract In this study we described the seed rain generated by bats under four Cerrado’s tree species common within pastures, Buchenavia tomentosa, Couepia grandiflora, Licania humilis and Qualea grandiflora. We analyzed the similarity among the four tree species in terms of seed rain composition, and compared the number of seeds and seed species deposited under them. Besides that, we assessed the relationship between seed rain intensity and the density of each tree species. Then, we randomly selected 10 mature trees of each species to sample seed rain. We recorded a total of 4892 bat dispersed seeds from 11 species. Also, we observed that along the year seed deposition varied substantially under all trees. At least two seed sub-communities could be distinguished according to tree species used by bats as feeding roost. One related to Couepia grandiflora and Licania humilis, and the other to Buchenavia tomentosa and Qualea grandiflora trees. The variability of seed rain composition in any particular tree and the range of actual seed fall into a particular species indicate patchiness in seed rain, and the overall results appear to be consistent in terms of a substantial and diverse seed rain generated by bats in a highly anthropized landscape. This is the first study concerning seed dispersal by bats in modified Brazilian Cerrado, one of the most endangered biomes in the world. In this respect, by preserving a dense and diverse collection of remnant trees within today's pastures may, potentially, contribute to a faster Cerrado recovery in extensive areas that can be reclaimed for restoration in the future.